Semiotic space invasion: The case of Donald Trump's US presidential campaign - Wignell, Peter; O'Halloran, Kay; Tan, Sabine (De Gruyter Mouton, 2019)
© 2019 Walter de Gruyter GmbH, Berlin/Boston. This paper uses a social semiotic perspective to analyze Donald Trump's domination of media coverage of the US presidential campaign from 16 June 2015, when he announced his candidacy for nomination as the Republican candidate until 8 November 2016, when he was elected as President of the United States. The paper argues that one of the keys to Donald Trump's domination of media coverage was that, in presenting himself and his agenda, he foregrounded interpersonal meaning by making himself the focus of attention of the campaign through strategies that invaded various semiotic spaces to form a "sub-semiosphere" of Trump dogma. The effects of this were that what he did and what he said captured the majority of media attention at the expense of his opponents, enabling him to win the election, despite his complete lack of background experience as a politician.